Pengembangan Jiwa Wirausaha Anak Panti Asuhan Melalui Pelatihan Pembuatan Keychain di Yayasan Mizan Amanah Krukut - Nadia Oktaviani; Najwa Windiyanti; Risma Melati (CV Edujavare Publishing, 2025)
This community service program aims to develop the entrepreneurial spirit of children at Mizan Amanah Orphanage, Krukut, through keychain-making training. Limited access to entrepreneurial education has caused orphanage children to lack creativity, business insight, and economic independence skills. The method used in this program was participatory training, which included entrepreneurial motivation sessions, practical keychain production training, simple cost calculation, and product marketing introduction. The results show that participants experienced increased motivation, creativity, and understanding of basic entrepreneurship concepts. Children were able to produce keychains with selling value and understand simple business opportunities. This program contributes positively to fostering an entrepreneurial mindset and can serve as an alternative empowerment model for orphanage children.